Bioinspired monolithic polymer microsphere arrays as generically anti-adhesive surfaces. (17th March 2016) - Eichler-Volf, Anna; Kovalev, Alexander; Wedeking, Tim; Gorb, Elena V; Xue, Longjian; You, Changjiang; Piehler, Jacob; Gorb, Stanislav N; Steinhart, Martin
Abstract: Bioinspired surface topographies showing generic anti-adhesive behaviour by minimization of the real contact area not only with rigid, but also with soft and compliant counterpart surfaces recently attracted increasing attention. In the present study, we show that such generic anti-adhesive surfaces, which moreover demonstrate anti-fouling behaviour, can be produced on a large scale by a simple double replication of monolayers of microspheres with diameters of a few 10 μ m. Thus, we obtained mechanically stable monolithic arrays of microspheres tightly connected to a support of the same material. Adhesion of these microsphere arrays to sticky and compliant counterpart surfaces was one order of magnitude weaker than that of flat control samples of the same material. The generation of nanorod arrays with nanorod diameters of a few 100 nm as the second hierarchical structure level on monolithic microsphere arrays did not significantly affect the adhesion force. The experimental data on anti-adhesive behaviour were modelled using a modified Johnson–Kendall–Roberts theoretical approach that also provided general design criteria for topographic adhesion minimization to sticky counterpart surfaces.